Investigation of hydroelectric station workshop layout using simulation technique / Fatimah Rusliahty Ahmad - Ahmad, Fatimah Rusliahty (2009)
This study presents a new improved layout workshop design of Tenaga Nasional Berhad Stesen Janaelektrik Sultan Mahmud, Kenyir, Terengganu. The current layout and working condition of the workshop have been investigated before co~ing out with the proposed new layout design. The actual layout will be translated into virtual layout using CATIA software. Then, the actual layout will be compared to the new improved layout design and all factors such as time, space, cost and safety are considered significant in this study. Based on the analyzed results, some recommendations are proposed to improve the workshop layout and working condition. Thus, the best recommendation could be useful to the company to improve the overall layout and also the working condition of the current workshop